PayTech and the d(ata) n(etwork) a(ctivities) of BigTech platforms - Jonathan Chiu; Thorsten V. Koeppl (Queen's University, Department of Economics, 2022)
Why do BigTech platforms introduce payment services? Digital platforms often run business models where activities on the platform generate data that can be monetized off the platform. There is a trade-off between the value of such data and the privacy concerns of users, since platforms need to compensate users for their privacy loss by subsidizing activities. The nature of complementarities between data and payments determines the introduction of payments. When data help to provide better payments (data-driven payments), platforms have too little incentives to adopt. When payments generate additional data (payments-driven data), platforms may adopt payments inefficiently.
Keywords: D8; E42; L1; 330; BigTech; Payments; Privacy; Digital Platform; Data